2017
DOI: 10.3892/mmr.2017.8073
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of microRNA-146 protects against oxygen-glucose deprivation/recovery-induced cardiomyocyte apoptosis by inhibiting the NF-κB/TNF-α signaling pathway

Abstract: MicroRNA (miR) has been reported to be associated with ischemia and reperfusion (I/R) and cell apoptosis. Suppression of cell apoptosis may reduce the irreversible damage induced by reperfusion. The aims of the current study were to explore the cytoprotective effects of miR-146 against oxygen-glucose deprivation/recovery (OGD/R)-induced injury in H9c2 rat myocardial cells, as well as the underlying mechanisms. Following stimulation with OGD/R, the cells were transfected with miR-146 mimics or negative controls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 41 publications
1
15
0
Order By: Relevance
“…Studies have shown that NF-κB signaling was related to apoptosis. That is to say, high activity of NF-κB signaling could cause anti-apoptosis in cancer cells [ 52 54 ]. Therefore, suppression of NF-κB signaling was probably responsible for Andro-induced apoptosis in MCF-7, which could also inhibit COX-2 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that NF-κB signaling was related to apoptosis. That is to say, high activity of NF-κB signaling could cause anti-apoptosis in cancer cells [ 52 54 ]. Therefore, suppression of NF-κB signaling was probably responsible for Andro-induced apoptosis in MCF-7, which could also inhibit COX-2 expression.…”
Section: Discussionmentioning
confidence: 99%
“…The present study demonstrated that BAC induction of DED provoked NF-κB activation, which was markedly suppressed by topical CsA, consistent with decreased expression of inflammatory mediators. We suggest that CsA suppression of NF-κB signalling may down-regulate expression of inflammatory molecules, including cytokines such as IL-1β [3840], TNF-α [40, 41] and IL-6 [40, 42, 43], and chemokines [4446] such as ICAM-1 and VCAM-1.…”
Section: Discussionmentioning
confidence: 99%
“…This synergistic effect might be due to the fact that each of the aforementioned miRNAs inhibits p38-caspase3-induced apoptosis via different mechanisms [98,99] (Figure 4). For instance, miR-21 attenuates cardiomyocyte injury via regulating the programmed cell death 4 (PDCD4) and AKT pathway, whereas miR-146a exerts its protective antiapoptotic effects through modulating interleukin-1 receptor-associated kinase1 (IRAK1), tumor necrosis factor (TNF) receptor-associated factor 6 (TRAF6) and the NF-κB/TNF-α pathways [100,101,102]. This finding opens the window to a potential synergistic effect of multiple miRNAs and their impact on disease prevention or progression [57].…”
Section: Micrornas (Mirnas)mentioning
confidence: 99%